The diabetic-anemia nexus: implications for clinical practice - Ahmed, Ghada M; Abed, Mohammed N; Alassaf, Fawaz A (Vojenské zdravotnické listy, 2024)
Objectives: Due to a variety of factors, individuals with diabetes are more likely to develop anemia. Chronic kidney disease, a frequent consequence of diabetes, is one of the key contributing factors. Diabetic neuropathy is another reason that can result in gastrointestinal bleeding and iron malabsorption. Healthcare providers must be aware of the connection between diabetes and anemia in order to closely monitor and treat both disorders and lessen their detrimental effects on general health and quality of life. This review sought to explore the underlying factors that lead to anemia in diabetic individuals, as well as the most prevalent kinds of anemia and suggested management approaches.Methods: PubMed, Cochrane Library and Google scholar were searched to find all relevant articles published in English until October 2023, using the specified search phrases, and we then brought up and analyzed all of the papers that matched the requirements.Results and conclusion: Collectively, managing anemia in diabetes patients is a difficult issue that calls for a multimodal approach. Early detection and effective therapy of anemia in diabetic patients depend on routine monitoring of the blood levels of hemoglobin, glycemic control, blood pressure, foot health, renal and retinal functions, neuropathy, and other comorbidities.
Keywords: Erythropoiesis; Anemia; chronické selhání ledvin; Diabetic Neuropathies; diabetes mellitus; lidé; gastrointestinální krvácení; erytropoéza; Gastrointestinal Hemorrhage; Kidney Failure, Chronic; deficit železa; Risk Factors; Diabetes Complications; rizikové faktory; Diabetes Mellitus; anemie; komplikace diabetu; diabetické neuropatie; Iron Deficiencies; Humans